Characterization of the complete mitochondrial genome of the Sunda stink-badger (Mydaus javanensis) from the island of Borneo - Subbiah,Vijay Kumar; Gomez,Chrishen Robert; Robben,Dexter Miller; Subramaniam,Ranjita; Hearn,Andrew James (PeerJ, 2024)
Background The Mephitidae is a family of skunks and stink-badgers that includes 12 extant species in four genera, namely, Mydaus, Conepatus, Mephitis and Spilogale. Mydaus is the only genus within Mephitidae found outside the American continent, with its distribution limited to the islands of Borneo, Indonesia and Philippines. There are two extant species of Mydaus i.e., javanensis and marchei. Currently, complete mitogenomes are unavailable for either species. Here, we present the characterization of the first complete mitogenome for the Sunda stink-badger (Mydaus javanensis) from the island of Borneo. Methods Muscle tissue was obtained and the DNA was sequenced using a combination of Illumina Barcode Tagged Sequence (BTSeq) and Sanger sequencing techniques. The genome was annotated with MITOS and manually checked for accuracy. A circular map of the mitogenome was constructed with Proksee. Relative synonymous codon usage (RSCU) and codon frequency were calculated using MEGA-X. The protein coding genes (PCGs) were aligned with reference sequences from GenBank and used for the construction of phylogenetic trees (maximum liklihood (ML) and Bayesian inference (BI)). Additionally, due to the lack of available complete genomes in public databases, we constructed another tree with the cyt b gene. Results The complete circular mitogenome was 16,391 base pairs in length. It comprises the typical 13 protein-coding genes, 22 tRNAs, two ribosomal RNA genes, one control region (CR) and an L-strand replication origin (OL). The G+C content was 38.1% with a clear bias towards A and T nucleotides. Of the 13 PGCs, only ND6 was positioned in the reverse direction, along with five other tRNAs. Five PCGs had incomplete stop codons and rely on post-transcriptional polyadenylation (TAA) for termination. Based on the codon count, Leucine was the most common amino acid (589), followed by Threonine (332) and Isoleucine (325). The ML and BI phylogenetic trees, based on concatenated PCGs and the cyt b gene, respectively, correctly clustered the species with other members of the Mephitidae family but were unique enough to set it apart from Conepatus, Mephitis and Spilogale. The results confirm Mydaus as a member of the mephitids and the mitogenome will be useful for evolutionary analysis and conservation of the species.
Keywords: Mephitids; Skunk; Mitogenome assembly; Comparative mitogenomics; Phylogenomics; Taxonomy